THE EFFECT OF EDUCATION AND TRAINING ON LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT SURACOJAYA ABADI MOTOR CAB SENTRAL YAMAHA MAKASSAR - Putra Rusdin, Andi Andika; Sinring, Bahar; Plyriadi, Annas (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to examine the effect of leadership style, work environment, and employee engagement as well as the influence of education and training, leadership style, and work motivation on employee performance at PT Suraco Jaya Abadi Motor Cabang Sentral Yamaha Makassar. The data for this research were obtained from employees at PT Suraco Jaya Abadi Motor Cabang Sentral Yamaha Makassar in 2025 who were willing to participate as respondents. This research used primary data by conducting direct field research, distributing questionnaires/statements to respondents, and applying the census sampling method. The census method was chosen because of the small population size, with the sample consisting of the entire population of only 67 employees. Data analysis was conducted using descriptive statistical analysis and SPSS 26.0. Based on the research findings, it can be concluded that leadership style, work environment, employee engagement, education and training have a positive and significant effect on employee performance. In other words, the better the education and training, the better the employee performance at PT Suraco Jaya Abadi Motor Cabang Sentral Yamaha Makassar. Leadership style also has a positive and significant effect on employee performance, meaning that improved leadership style leads to improved performance. Likewise, work motivation has a positive and significant effect on employee performance—the higher the motivation, the better the performance.